The Relationship between Oral and Dental Health Self-care and Hemoglobin A1c in Adults with Diabetes - Atousa Haghdoost; Soheila Bakhshandeh; Zahra Ghorbani; Mahshid Namdari (Shiraz University of Medical Sciences, 2022)
Statement of the Problem: Due to the mutual relationship between periodontal diseases and diabetes, it seems that adopting oral self-care in a way to prevent and control the progress of periodontal diseases, improves the oral health of diabetic patients as well as their general health. Purpose: The aim of this study was to investigate the relationship between the oral self-care behaviors and the hemoglobin A1c (Hb A1c) levels in adults with diabetes. Materials and Method: In this cross-sectional study with convenience sampling, 120 adults between 18 to 50 years old, who had at least two healthy functional teeth, were selected from private endocrinology offices in Tehran in August 2019. The exclusion criteria were illiterate individuals and pregnant women. A standard questionnaire was used which included the information about demographic, diabetes, and self-care behaviors. The outcome variable was the latest Hb A1c rate. Results: The mean age of participants was 35.8±10.5 years. The average Hb A1c was 7.4± 1.55%. 35.0% of participants brushed their teeth twice a day or more and 60.8% flossed rarely. The proportion of Hb A1c <7% was higher in three groups including the participants who had information about the effect of periodontal disease on diabetes (p= 0.032), participants who brushed twice a day or more (p= 0 .014), and those who used dental floss once a day or more (p< 0.001). The likelihood of having Hb A1c <7% in participants who had information about the effect of periodontal disease on diabetes was about three times more than those who had no information (OR= 3.05, p= 0.036). Furthermore, it was about six times higher in participants who used dental floss once a day or more than those who used rarely (OR= 5.66, p= 0.001). Conclusion: Results of the present study show that people who had better oral health self-care behaviors had better Hb A1c and diabetes control.